The Issue of Jadids of Turkestan and the Unity of the Turkish Nations (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
At the beginning of the 20th century, Kazakhs, Kyrgyz, Turkmen, and Tajiks worked side by side in the Turkestan resistance movement worked together with their Turkish, Tatar, and Azerbaijani brothers in reforming the education system and forming political associations. As a result, relations between Turkestan and Tatar developers developed, and modern schools began to open in central cities such as Tashkent, Bukhara, and Khiva. This article reflects the efforts made by Tatar and Kozna enlighteners such as Husayn Koshayev, Komila Koshayeva, Husayn Makayev, Zarif Muzaffari and Komila Muzaffaria for the unity of Turkic peoples.